Monitoring System for Hazardous Gas in Landfill Site Based on Internet of Things - Sugeng Purwantoro E.S.G.S; Wenda Novayani; Raviqa Sandra Putri (Politeknik Negeri Cilacap, 2023)
The landfill is a place where waste reaches the last stage in its management since it began to arise in the source, collection, transportation, processing, and disposal. Muara Fajar landfill is one of the landfills in Pekanbaru City whose garbage increase exceeds the capacity of waste storage land so that it can produce 800 tons of garbage per day in dry weather and 1000 tons per day in rainy weather. The problem caused by the management of the Muara Fajar landfill is air pollution due to the process of decomposing organic matter anaerobically which has the potential to cause unpleasant odors and health problems. With this problem, a system was built to monitor and detect hazardous gases in landfill, namely H2S gas using MQ-136 sensors, CH4 gas by MQ-4 sensors, and CO2 and NH3 gases using MQ-135 sensors. This system is implemented with the IoT protocol, MQTT Broker to receive and send monitoring data to the Website with notifications from the telegram web application. Based on testing the value of ppm in CO2 Gas with a danger status of 1000-4000 ppm, H2S Gas is 10-400 ppm, NH3 is included in the status of be careful which is 0.03 ppm, and CH4 with normal status because the value of ppm levels is below 10000 ppm